(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In this article absolute and relative export indicators of Ukrainian goods are analysed in general, as well as wood and wood products are examined in particular. The share of wood and wood products export in total export is determined. Export growth rates, indicators of the structure of export of wood and wood products according major product groups are calculated. The value of 1 ton of wood and wood products exports by major product groups is determined. The results of the research show that Ukrainian statistics of the export of wood and wood products in general as well as by product groups do not reflect the real market situation in this area. It depends on a number of objective and subjective reasons. In particular, there is an inconsistency in the system of current legislation of Ukraine (Customs Code – Forest Code) and a disparity in the classification and codification of commodities from wood after commodity groups. This inconsistency leads to illegal manipulations at the market and serve as false information, which is represented in the system of domestic statistics. Therefore, there is an urgent need to improve the Ukrainian classification of goods of foreign economic activity in accordance with international standards of forestry statistics, classifications and definitions of forest products of the Food and Agriculture Organization United Nations (FAO). This is necessary to ensure the reliability of information and eliminate the discrepancy between the data of Ukrainian statistics and statistics of other countries regarding export of wood and wood products. The results of the study of wood and wood products export for the period of 2010–2017 show a significant increase in 2011 compared to 2010, a slight decrease in 2012 and growth in 2013–2014 and 2016–2017. The rates of growth of export of goods in general and the products under investigation did not coincide and were worse only in 2011, 2012 and 2017. The share of untreated timber has decreased significantly in 2017 due to the introduction of a moratorium on the export of untreated timber in 2015. However, the shares of other raw material groups such as firewood have increased. The research of the structure of commodity groups export and the cost of 1 ton of products from these groups demonstrate the lack of efficiency and unproductive use of wood resources of the forest in Ukraine.